Time-lapse between periodontal regeneration surgery and root canal therapy in sever combined periodontal-endodontic lesions - Tingyan Dong; Yan Zhang; Xinyue Li (Saudi Dental Journal)
Objective: The purpose of this study was to evaluate the time-lapse of periodontal regeneration surgery of combined periodontal-endodontic lesions (PEL) after root canal therapy (RCT) to guide the clinical treatment. Methods: 26 patients (28 teeth) with severe combined PEL were equally divided into 4 groups (n = 7); the control group included patients who underwent periodontal regeneration surgery with no prior RCT and the remaining three experimental groups including patients who received periodontal regeneration surgery post-RCT either immediately or after 3 and 6 months. The probing depth, clinical attachment loss, and periodontal bone density were measured before or after 3, 6, and 12 months post-RCT, respectively. Results: Periodontal regeneration surgery could improve the PD (Probing Depth), CAL (Clinical Attachment Loss), BD (Bone Mineral Density) values irrespective of whether the RCT was performed within 12 months or not. However, obviously improved PD, CAL and BD were observed when surgery was performed post-RCT. The time lapse between RCT and periodontal regeneration surgery had no obvious effects on the periodontal index in 3 months after the surgery. Moreover, these periodontal indexes tend to stabilize in 3 to 6 months after the surgery with no significant differences. Conclusion: Although there were no obvious impacts of time lapse between RCT and periodontal regeneration surgery on the severe PEL, an earlier periodontal surgery might contribute to the healing of periodontal lesions.